The efficacy of axillary brachial plexus block plus axillary subcutaneous injection of local anesthetic versus axillary block alone for prevention of tourniquet pain in upper extremity surgery - Dabir, Shideh; Mosaffa , Faramarz; Toloeinia, Farnaz; Hosseini, Behnam (Researcher Bulletin of Medical Sciences, 2024)
Abstract Background and Objective: The ultrasound guided axillary block provides good anesthesia for orthopedic surgery below the elbow. However, an upper arm tourniquet may be painful because the block may not anesthetize the area under the inflated cuff. The aim of this study was to determine whether subcutaneous injection of a local anesthetic in the axilla decrease the incidence of tourniquet pain in orthopedic surgery performed under axillary block. Materials and Methods: 68 ASA I-III patients undergoing orthopedic surgery for forearm, wrist and hand under ultrasound guided axillary block entered into this prospective, randomized, double-blinded clinical trial. 34 axillary blocks in conjunction with a subcutaneous injection of lidocaine (study group) and 34 axillary blocks with subcutaneous saline injection (control group) were performed. The incidence and severity of tourniquet pain, tourniquet pain onset time, tourniquet inflation time, supplementary analgesia requirement for tourniquet pain and patient satisfaction were evaluated. Results: 16 women and 52 men, age of 17-70 years were included. The characteristics of the patients and operation and onset of tourniquet pain were similar in two groups. The incidence of tourniquet pain, pain scores at the tourniquet site, and the incidence of supplementary intravenous analgesia was significantly higher in the control group than in the study group. Conclusions: The incidence and severity of tourniquet pain with combining axillary brachial plexus block and a subcutaneous injection of lidocaine was significantly less than that associated with axillary block alone. It is an effective simple and safe method in prevention of tourniquet pain in the upper arm.